Efficacy of Akway (Drymis sp.) Bark Extract in Restoring Hemoglobin Levels: A Preclinical Study in a Sodium Nitrite-Induced Anemia Mice Model - Lukman Hardia; Fabanyo, Syahrul H.; Budiyanto, Angga Bayu; Muslihin, A. M.; Rossardy, Marzella Dea; Irwandi, Irwandi; Watora, Wahyuni (Farmasains : Jurnal Farmasi dan Ilmu Kesehatan, 2026)
The high prevalence of anemia prompted us to explore the potential of local herbs in Papua, Indonesia, which is known for its rich natural resources. In this study, we aim to conduct preclinical tests on anemia model test animals to validate the effectiveness of akway bark extract (ABE) as the basis for the development of effective and safe herbal antianemia drugs in the future. This study employs a quantitative analytical approach, utilizing an experimental design with a pre-posttest with a control group design. The research sample used 20 mice test animals, divided into 5 groups consisting of 4 animals each, namely: the control group (positive and negative), and the intervention group using ABE doses of 10, 30, and 50mg/kg. This study was approved by the Health Research Ethics Committee of STIFAR Makassar (Number: 299/EC.1.1.B/III/KEPK/2024). Data analysis showed that a 14-day intervention using ABE was able to increase Hb levels (D% = 52.00±27.13 [ABE dose 10mg/kg]; 49.72±7.86 [ABE dose 50mg/kg] and 42.82±12.75 [ABE dose 30mg/kg]) significantly (p<0.05) when compared with the negative control (D% = 4.54±5.14), but when compared with the positive control (D% = 52.57±10.85) the average increase in Hb levels was not significant (p>0.05). In conclusion, our study showed that mice of the anemia model, intervened using ABE at doses of 10, 30, and 50mg/kg once daily for 14 days, experienced increased Hb levels.